Achieving Work-Family Balance: An Action Regulation Model - Hirschi, Andreas; Shockley, Kristen M.; Zacher, Hannes (Academy of Management Review, 2019)
Work and family are highly intertwined for many individuals, yet individual-level strategies for achieving effectiveness and satisfaction across work and family roles have not received sufficient attention. We address this issue by conceptualizing work-family balance from an action regulation perspective as the successful joint pursuit of work and family goals. Building on insights from the work-family literature, action regulation theory, and multiple goals research, we propose a theoretical model that explains how people can jointly attain work and family goals by using four action strategies: allocating resources, changing resources and barriers, sequencing goals, and revising goals. We address the conditions under which each strategy is used, depending on the malleability of resources and barriers for goal attainment, time to deadline of goals, and feedback and monitoring of progress across work and family goals. Our model offers new insights into and research implications for work-family balance and helps develop practical interventions that result in improved management of the work-family interface.